Buddhist Education’ Quality through PAKEM - Sunter Candra Yana; Tejo Ismoyo; Wahyu Diono; Lamirin Lamirin; Eko Pramono (Budapest International Research and Critics University, 2022)
Buddhist education in Indonesia, have not fully progressed. This is not apart from conventional learning process, changing progress in the form of learning that more innovative. The learning process is active, effective, and fun (PAKEM), is the transformation of conventional learning. This learning directed learning in group that more innovative and proven effective in accordance with the Buddha’s method of teaching. Buddhist education’ quality, not a part of the learning processes that direct student to think critically. PAKEM be the right solution because according to the word of the Buddha, that in learning process student emphasized to more active and critical. The implementation of PAKEM’s model emphasizes learning in group. Human interact, interdependent, and need to learn in group, to gain experience of another person, person can learn and develop themselves. Buddha teaches His student to learn all the teachings together in group, and not make mischief. Thus, Buddhist education that have the following principal characteristics are comprehensive knowledge (pariyatti), learned into practice become the guidance of behavior (patipatti) and achieve of dharma’s truth (pativedha)